PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DISERTAI KUIS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI IPA SMAN 1 LUHAK NAN DUO KABUPATEN PASAMAN BARAT TAHUN PELAJARAN 2013/2014 - Zulistia, Febrina; Rismen, Sefna; Lovia, Lita (STKIP PGRI Sumbar, 2013)
The background of is Understanding of mathematical concept is low. This research is knowing whether the studentsâ mathematical concept apprehension by applying the cooperative learning model of Think Pair Share type, accompanied by questionnaire, was better than the students understanding of mathematical concept by applying the conventional learning at SMAN I Luhak Nan Duo in Pasaman Barat Regency. This was experimental research with experimental design of Random to Subject. The instruments used in this research was questionnaires and final tests. The results of student activity analysis show that the activities risen Â an improvement, and from the hypothesis testing it is obtained that P-value is 0.005 so that H0 is rejected and the hypothesis is accepted. It can be summarized that the students understanding of mathematical concept by applying the think-pair-share-type cooperative learning model with the questionnaires was better than that by using the conventional one for the XI-grade IPA student of SMAN I Luhak Nan Duo, Pasaman Barat Regency, academic year 2013/2014.